Infecção latente em coelhos inoculados com o herpesvírus bovino tipo 5 (BHV-5): reativação, excreção viral e recrudescência da enfermidade neurológica - Caron, Luizinho (2001)
Weanling rabbits are highly susceptible to bovine herpesvirus type-5 (BHV-5) and after experimental infection often develop an acute fatal neurological disease. To determine whether acute infection is followed by the establishment of latent infection, older rabbits (3-4 and 5-6-months-old), which are less susceptible to acute neurological infection, were inoculated by the intranasal or conjunctival routes with two south american BHV-5 isolates (613 and EVI-88). Eight rabbits (8/27) incoculated with isolate 613 and one (1/34) inoculated with isolate EVI-88 developed neurological disease and died during acute infection a few days after inoculation. In addition, three rabbits developed neurological disease and died 34, 41 and 58 days after virus inoculation. Fifty six to 62 days after inoculation, the remaining rabbits were submitted to dexamethasone (Dx) administration to reactivate the infection. Twenty five out of 44 rabbits (56.8%) shed virus in nasal or ocular secretions after Dx treatment. The frequency and course of virus shedding varied with the virus isolate, route of inoculation and Dx dose. Virus shedding was first detected at day two post-Dx treatment (dpDx) and lasted from one to eleven days (average 2.8 days). The frequency of virus reactivation and shedding was higher among rabbits inoculated with isolate 613 (12/16 or 75%) than among rabbits inoculated with isolate EVI-88 (13/28 or 46.4%). Virus reactivation upon Dx administration was accompanied by neurological signs in nine rabbits (20.4%), resulting in six deaths (13.6%). The neurological signs resembled those observed during acute infection; started as early as at day 3 pDx and lasted from less than 24 hours to twelve days. In addition, three rabbits showed signs of neurological infection followed by death 31 to 54 days after Dx treatment. Infectious virus, viral nucleic acids and inflammatory changes were detected in the brain of these rabbits. The late onset of clinical disease after acute infection or Dx administration some rabbits suggests these animals experienced a spontaneous or a delayed-onset Dx-induced viral reactivation and recrudescence of neurological disease. These results demonstrate that BHV-5 does establish a spontaneously and chemically reactivatable latent infection in rabbits after acute infection. Reactivation of latent infection courses with virus shedding and frequently with recrudescence of neurological disease. Further studies in rabbits may help understanding the neuropathogenesis of BHV-5 latent infection in cattle.